(3GdbQWGS aj CNHGQ edhc GdeZQH hHfGA eOjfI aGSs - (3Ydj Hf YHO Gddg (B((3Ch GHf eMeO(B) (3Hf CMeO Hf YeQ GHf CHj RQY GdaGSj,J (B741 (3g` s
(3ChdgG (B:s
(3Ce HYO , CWGd Gddg HbGA ehdGfG GdNdjaI GdEeGe HJCdja cJGH LGeY dWja ai GdCNHGQ hedM GdBOGH jMJhi Ydi ZQQ ef GdJGQjN hYLGFHg HNjQ HfHP ef CNHGQ edhc GdeZQH GdeJbOejf s
(3BNQgG (B:s
(3hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjekG cKjQkG s
(3hQOJ CjVkG JMJ YfhGf GdeZQH GdeHjf YeG JVefg GdCfjS GdeWQH hQhVI GdeaSQjf (B" (3HQbe (B" 2039"s
(3hcPdc hQO GSeg Ydi GdUaMI GdChdi ef GdfSNI GdeWHhYI hGfXQ GdNdGa ai Pdc ai GdCYdGe (B5: 126s
(3hHCKfGFgG ChQGb cJHJ HNW eZGjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B305 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B181s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B322 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B199s
Keywords: (3GdJGQjNs